The Impact of Attending an Independent Upper Secondary School: Evidence from Sweden Using School Ranking Data - Karin Edmark; Lovisa Persson (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper provides a comprehensive study on how attending a Swedish independent upper secondary school, instead of a public school, affects students' academic and short-term post-secondary outcomes. We apply two estimation methods to data on upper secondary applicants: 1) A value-added model (VAM), where we, in addition to detailed student background characteristics, also control for student preferences for independent provision, as stated in the application forms. 2) A regression-discontinuity (RD) estimation around admission cutoffs to independent versus public schools. As the RD-results are overall too imprecise to provide much guidance, they are presented in an appendix to the paper. The more precisely estimated results using VAM suggest a positive independent school effect on: final GPA, test results in English and Swedish, the likelihood of graduating on time, and attending post-secondary education. We however also find indications of more lenient grading practices among independent schools, and we cannot rule out that all of the independent school advantage reflects more generous grading standards. Results from a school level analysis reveals that the average independent school impact masks substantial variation. Notably, schools with a higher share of qualified teachers tend to exhibit smaller GPA-gains, but also show signs of adhering to stricter grading standards.
Keywords: H44; I21; I26; I28; 330; private provision; mixed markets; voucher school reform; upper secondary education